Deciphering the Epigenetic Code of Cardiac Myocyte Transcription. Issue 5 (14th August 2015) - Preissl, Sebastian; Schwaderer, Martin; Raulf, Alexandra; Hesse, Michael; Grüning, Björn A.; Köbele, Claudia; Backofen, Rolf; Fleischmann, Bernd K.; Hein, Lutz; Gilsbach, Ralf
<x xml:space="preserve">Abstract</x> Rationale: Epigenetic mechanisms are crucial for cell identity and transcriptional control. The heart consists of different cell types, including cardiac myocytes, endothelial cells, fibroblasts, and others. Therefore, cell type–specific analysis is needed to gain mechanistic insight into the regulation of gene expression in cardiac myocytes. Although cytosolic mRNA represents steady-state levels, nuclear mRNA more closely reflects transcriptional activity. To unravel epigenetic mechanisms of transcriptional control, cell type–specific analysis of nuclear mRNA and epigenetic modifications is crucial. Objective: The aim was to purify cardiac myocyte nuclei from hearts of different species by magnetic- or fluorescent-assisted sorting and to determine the nuclear and cellular RNA expression profiles and epigenetic marks in a cardiac myocyte–specific manner. Methods and Results: Frozen cardiac tissue samples were used to isolate cardiac myocyte nuclei. High sorting purity was confirmed for cardiac myocyte nuclei isolated from mice, rats, and humans. Deep sequencing of nuclear RNA revealed a major fraction of nascent, unspliced RNA in contrast to results obtained from purified cardiac myocytes. Cardiac myocyte nuclear and cellular RNA expression profiles showed differences, especially for metabolic genes. Genome-wide maps of the transcriptional elongation mark H3K36me3 were generated by chromatin-immunoprecipitation. Transcriptome and epigenetic data confirmed the high degree of cardiac myocyte–specificity of our protocol. An integrative analysis of nuclear mRNA and histone mark occurrence indicated a major impact of the chromatin state on transcriptional activity in cardiac myocytes. Conclusions: This study establishes cardiac myocyte–specific sorting of nuclei as a universal method to investigate epigenetic and transcriptional processes in cardiac myocytes of different origins. These data sets provide novel insight into cardiac myocyte transcription.